DISKURUS KOMPILASI HUKUM ISLAM (KHI) DALAM SISTEM HUKUM INDONESIA - Marpaung, Watni (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2023)
Abstract: Compilation of Islamic Law (KHI) is a product of Indonesian Islamic law. The inevitability of legal changes and developments is something that cannot be denied. The originality of the contents of the Compilation of Islamic Law (KHI) reflects the legal dynamics that live and develop in the midst of Indonesian Islamic society. The contribution that has been played in the legal context system in Indonesia has had a significant impact on the development of law in Indonesia.Kata kunci: Kompilasi Hukum Islam (KHI), Sistem Hukum